The acute-to-chronic glycemic ratio correlates with the severity of illness at admission in patients with diabetes experiencing acute ischemic stroke - Liu, Chao; Zhu, Xu-ping; Zhu, Xiao-wei; Jiang, Yan-min; Xi, Guang-jun; Xu, Lan (Frontiers in Neurology, 2022)
Acute hyperglycemia is a powerful indicator of the severity of acute ischemic stroke (AIS); however, the relationship between these two factors is not very clear in patients with diabetes. We aimed to retrospectively evaluate data from 335 consecutive patients who experienced AIS from November 2015 to November 2016 to investigate whether a comprehensive assessment of blood glucose levels is a more valuable indicator of the severity of AIS or the presence of acute hyperglycemia in patients with diabetes. We collected demographic data, clinical manifestation information, clinical scores, and laboratory data [including fasting blood glucose and glycated hemoglobin (HbA1c) levels]. We estimated prehospital mean blood glucose concentrations using the following formula [1.59 * HbA1c (%) – 2.59] to calculate the “Acute-to-Chronic Glycemic Ratio” (AC ratio). The AC ratio differed significantly among patients grouped according to the National Institutes of Health Stroke Scale/Score (NIHSS) at admission (admission NIHSS) (p = 0.006). Univariate regression analysis revealed a correlation between the AC ratio and admission NIHSS [standardized β-coefficient (Std. B) = 0.164, p = 0.004]. The adjusted linear regression analysis revealed a correlation between both HbA1c (Std. B = 0.368, p = 0.038) and the AC ratio (Std. B = 0.262, p = 0.022) and admission NIHSS. The AC ratio (Std. B = 0.161, p = 0.012) was related to admission NIHSS in the stepwise variable selection. For an admission NIHHS > 4, the AC ratio (Std. B = 0.186, p = 0.047) was related to admission NIHSS in the stepwise variable selection. The AC ratio (Std. B = 1.163, p = 0.006 and Std. B = 0.565, p = 0.021, respectively) were related to admission NIHSS in both large-artery atherosclerosis (LAA) and small-vessel occlusion (SVO) subgroups. Thus, the AC ratio is related to admission NIHSS in patients with diabetes who experienced AIS and may be a better indicator of severity than acute blood glucose levels.